Limits and chances in an unfortunate course of recurrent orbital rhabdomyosarcoma - Rustemeyer, J; Günther, L; Junker, L (Nepalese Journal of Ophthalmology, 2011)
Background: Orbital rhabdomyosarcoma (RMS) in childhood has an excellent survival rate after chemotherapy and radiation, and mutilating surgery can often be avoided. Case report: As a rarity we present an unfortunate disease course in a child suffering from orbital embryonal RMS which did not enduringly respond to multimodal therapy including local excision and exenteration orbitae. After short intervals and despite tumor-free margins, orbital RMS recurred twice and led to an extended exenteration orbitae including the bony margins. Because of the lack of standards for adjuvant therapy in cases of recurrences after exenteration orbitae, therapy had to be restricted to a wait- and- see strategy as the only chance of tumor control. Conclusion: Although survival rates of orbital RMS are high, the possibility of recurrence should not be underestimated. In cases of refractory RMS, new concepts are needed to offer further chances for survival. Key words: Orbital rhabdomyosarcoma, recurrence, orbital exenteration DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5279 Nepal J Ophthalmol 2011; 3(2): 202-205